WANPRESTASI DALAM PENGADAAN JASA KONSTRUKSI - Ibnul Watoni; Edshafa Muharatulloh; Ravee Jevon Susanto (Jurnal HUKUM BISNIS, 2022)
Developments in development today are increasing not only in urban areas but in rural areas, development continues to be intensified for the sake of creating smooth community mobility, one of which is through construction services. In the procurement of construction services, it is determined that an agreement and/or contract must be entered into to bind the construction object. The basis for carrying out construction through contracts is not only carried out by the private sector but can also be carried out by the government. It becomes a problem when the procurement of construction services does not pay attention to the substance of the contract, causing one of the parties to default, especially if there has been a court decision that has obtained permanent legal force. The formulation of the problem proposed by the author is what are the characteristics of default in the procurement of construction services as stated in Decision No. 01/Pdt.G/2019/PN.Jkt.Sel and how is the legal protection in case of default in the procurement of construction services. The research conducted by the author uses normative legal research using a statutory approach and a case approach. The results of this study are that the characteristics of default in the procurement of construction services must refer to the contract of both parties and the indicator is that one party feels aggrieved by the actions of the other party and legal protection in the event of a default in the procurement of construction services is the party who feels aggrieved can request cancellation of the agreement. accompanied by reimbursement of costs, losses and interest payments. Key words : Construction Services, Default, legal protection